Usability Analysis of Business Intelligence Tool Based Table Virtualization - Muh Zia ul Haq; Suharjito Suharjito (Institute of Advanced Engineering and Science, 2018)
The use of Business Intelligence for Small-Mid Enterprise (SME) no longer impeded by the size of the resources required. The study in this paper provides an overview of how the use of proposed software can be used as an effective and efficient alternative solution in building BI Tools combined with table virtualization utilization in SQL. To know the level of usability and suitability of the developed BI Tool, the researcher conducted evaluation and analyzation using 2 (two) tools (Heuristics Evaluation and UMUX-Lite). The result found the comparison between the output (Business Intelligence Tool) produced by PHP Report Maker has a better level of usability and suitability than its competitors. Although both are in a decent median, the output needs preferences and customizations to achieve maximum functionality like well-known other development software.